Characterization of Contact Structure for Woven Electronic Textile Using Conductive Polymer Micro‐Cantilever Array. Issue 1 (6th December 2013) - Yamashita, Takahiro; Khumpuang, Sommawan; Miyake, Koji; Itoh, Toshihiro
SUMMARY: A conductive polymer‐coated micro‐cantilever array made by the reel‐to‐reel continuous fiber process for use as an electrical contact component for woven electronic textile was investigated. We report a novel cantilever releasing method using air injection and the results of patternable CYTOP and organic conductive polymer using the nanoimprinting method. The conductive organic material used in this study was PEDOT:PSS [poly(3, 4‐ethylenedioxythiophene) poly(4‐styrenesulfonate)]. A micro‐cantilever contact array was realized to compose the electrical circuit through the large area woven textile. A contact resistance of 480 Ω was maintained for over 500 times. Contact resistance measurements revealed that an electric current begins to flow with smaller contact force in PEDOT:PSS‐coated cantilever array structure than in PEDOT:PSS film structure. There is no appreciable wear on the cantilever surface due to its movability after 103 cycles of contact testing with 0.5 N contact force. Based on these results, PEDOT:PSS‐coated micro‐cantilever arrays have excellent potential as electrical contact components between weft and warp for woven electronic textiles. © 2013 Wiley Periodicals, Inc. Electron Comm Jpn, 97(1): 48–53, 2014; Published online in Wiley Online Library (wileyonlinelibrary.com ). DOI 10.1002/ecj.11485